2020
DOI: 10.1177/0022034520913242
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Based Regenerative Endodontics for Treatment of Periapical Lesions: A Randomized, Controlled Phase I/II Clinical Trial

Abstract: A randomized controlled phase I/II clinical trial was designed to evaluate the safety and efficacy of encapsulated human umbilical cord mesenchymal stem cells in a plasma-derived biomaterial for regenerative endodontic procedures (REPs) in mature permanent teeth with apical lesions. The trial included 36 patients with mature incisors, canines, or mandibular premolars showing pulp necrosis and apical periodontitis. Patients were randomly and equally allocated between experimental (REP) or conventional root cana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
148
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(151 citation statements)
references
References 34 publications
1
148
0
2
Order By: Relevance
“…Thus, this study demonstrates better efficacy and safety of DPSCs implantation in cell-based REPs, in which 3-D dental pulp tissue with vasculature and innervation was regenerated. Besides, the efficacy and safety of allogenic umbilical cord MSCs have been proved in a preclinical trial ( Brizuela et al, 2020 ). Other cell populations, such as SCAP or non-dental cells might also be useful in cell-based REPs.…”
Section: Cell-based Repsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, this study demonstrates better efficacy and safety of DPSCs implantation in cell-based REPs, in which 3-D dental pulp tissue with vasculature and innervation was regenerated. Besides, the efficacy and safety of allogenic umbilical cord MSCs have been proved in a preclinical trial ( Brizuela et al, 2020 ). Other cell populations, such as SCAP or non-dental cells might also be useful in cell-based REPs.…”
Section: Cell-based Repsmentioning
confidence: 99%
“…The immunomodulatory effects of allogeneic MSCs are suggested to be of importance in inflammatory disorders. Allogenic umbilical cord MSCs have been used for mature permanent teeth with combination of plasma-derived biomaterials, showing acceptable safety and efficacy in a phase 1/2 clinical trial ( Brizuela et al, 2020 ). Although transplantation of allogeneic MSCs in REPs shows promising prospects, more research is needed regarding immunogenicity, long-term outcomes, and safety.…”
Section: Cell-based Repsmentioning
confidence: 99%
“…456 The recent results of the first randomized, controlled phase I/II clinical trial for delivery of mesenchymal stem/stromal cells (MSCs) encapsulated in platelet-poor plasma (PPP) showed that PPP/MSC treatment increased pulp response compared to a non-regenerative endodontic control. 457 A wide array of manufactured, biomolecule-based scaffolds has been used for pulp and dentin-pulp complex regeneration. 458 Indeed, the range of biomolecules used for pulp regeneration encompasses the range of biomolecules highlighted in this review.…”
Section: Pulp Regenerationmentioning
confidence: 99%
“…Very few clinical trials have been published on pulp regeneration 23,82,83 . Nakashima et al 23 published studies on the potential of mobilized DPSCs to regenerate pulp in dog pulpectomized teeth, and on this basis, they have initiated a clinical trial, making a reality the standardization and establishment of regulatory guidelines for SC therapy in clinical endodontics.…”
Section: Status Of Atmp-based Treatments In Regenerative Dentistrymentioning
confidence: 99%
“…It should be mentioned that although the authors supported cell expansion to take place under current GMP conditions, conventional research-grade media and supplements have been used; nevertheless, all patients passed the safety evaluation assessments. In another welldesigned RCT by Brizuela et al 83 they applied umbilical cord-derived MSCs encapsulated in a plasma-derived biomaterial for regenerative endodontic procedures (REPs) (n 5 18), while the control group (n 5 18) received conventional root canal treatment. The results proved the safety of the REP method, while both groups showed 100% efficacy at 12 months, defined as tooth remaining in the mouth with no percussion pain and an apical bone lesion of equal size, decrease, or no more than a 0.1-mm increase.…”
Section: Status Of Atmp-based Treatments In Regenerative Dentistrymentioning
confidence: 99%